Derrida’s restlessness: Heidegger and “letting be” in Donner le Temps II - Rocha, Delmiro (Escritura e Imagen, 2023)
This article deals with the analysis that Jacques Derrida carried out, in the Donner le temps II seminar, about the Heideggerian concept of Lassen. Is it possible to let the other be? Can we think of a “letting be” that does not mean abandonment? The article focuses the analysis on the seventh session of Derrida’s seminar and tries to account for the interest in deconstruction in Heidegger’s thought of the gift. Is Gelassenheit ontologically possible? What is the relationship between Derrida’s “laisssantrester” and Heidegger’s “Gelanssenheit”? What does it mean to be calm?